Association between pH regulation of the tumor microenvironment and immunological state - Hosonuma, Masahiro; Yoshimura, Kiyoshi (Frontiers in Oncology, 2023)
The tumor microenvironment (TME) is characterized by interactions among various cells, including tumor cells, immune cells, stromal cells, and blood vessels mediated by factors such as cytokines and metabolites. The development of cancer immunotherapy in recent years has facilitated a more comprehensive understanding of the TME. The TME changes with cancer type and host immune status, as well as with therapeutic intervention. However, studies on pH regulation of the TME have been mostly based on lactate, a metabolite of tumor cells. Notably, the Warburg effect results in the increased production of secreted lactate, thereby acidifying the extracellular microenvironment and affecting the surrounding cells. Lactate inhibits the activation and proliferation of CD8+ T cells, M1 macrophages, natural killer (NK) cells, and dendritic cells, contributing to tumor cell immune escape. It is also involved in angiogenesis and tissue remodeling, as well as promotes tumor growth and invasion. In this review, we have discussed the lactate-based pH regulation in tumor cells in the TME and its effects on the other constituent cells.